(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objective: To determine the frequency of risk factors for developmental dysplasia of hip (DDH) in patients presenting to a tertiary care hospital. Methods: This cross-sectional study was conducted in Department of Orthopedics and Trauma of Khyber Teaching Hospital (KTH), Peshawar from 26th October 2020 to 26th April 2021. Parents of all children with DDH fulfilling the inclusion criteria were interviewed for identifying risk factors for DDH. Data stratification was done for comparison of important variables. Statistical significance was determined by calculating P value with Chi square test and Fischer exact test. P values < 0.05 was considered significant. Results: In this study 163 children with DDH were included. The mean age was 7.56±3.357 years. Males were 91(55.8%) and female were 72(44.2%). History of oligohydramnios was noted in 43 (26.385) children and breach presentation in 34(20.9%). Pre term children were 23 (14.11) and post term 22 (13.50). Family history was positive in 17 (10.43) children. The frequency of DDH was more in female children with full term and in male children with post term and positive family history (P<0.05) Conclusion: Oligohydramnios, breach presentation and preterm delivery were the most frequently noted risk factors present in more than half of our patients of DDH in our series.